Functional outcomes and health-related quality of life after severe traumatic brain injury: A review - Mohamed Ludin, Salizar; Abdul Rashid, Nor'ain (SAGE Publications, 2018)
Throughout recovery, patients with severe traumatic brain injury (TBI)show physical and functional improvement but continue to have cognitive and psychosocial problems. The aim of this article was to review the literature regarding the functional and health-related quality of life (HRQOL) outcomes in severe TBI. There were 15 articles reviewed, 13 of them were quantitative studies and two were narrative review. Most of the articles showed an improvement occurs rapidly at 6 months post-injury. There were several factors that influence the outcome after TBI, most of it was the Glasgow Coma Scale (GCS) on admission, age, educational level, duration of posttraumatic amnesia (PTA), and length of stay (LOS) in the Intensive Care Unit (ICU). Thus, health care workers should help the survivors of severe TBI in the recovery process to ensure the latter can attain maximum function and quality of life.